Obce wcielenia Dusiołka. Leśmianowskie „cudotwory słowotwórcze” w przekładach anglojęzycznych - Wieczorkiewicz, Aleksandra (My University, 2016)
Bolesław Leśmian is an impossible writer – as Edward Balcerzan put it, “a poet with no masters, a master with no followers.” Moreover, he is usually considered untranslatable: the creator of his own idiomatic language, fraught with neologisms, archaisms, and dialectisms and subjected to the rigours of rhythm and rhyme, permeated with philosophical thought and vivid colours of the Slavic world – in short, an evident proof of the existence of the phenomenon known as untranslatability. But is it quite so? The main objective of the article is to present some difficulties connected with translating Leśmian’s poety into English, using the example of the translations of Leśmian’s ballade “Dusiołek” (by Rochelle Stone, Marian Polak-Chlabicz, and Krzysztof Bartnicki), and to compare the translation strategies adopted by their authors.
Keywords: Bolesław Leśmian; Polish poetry; English translations; literary translation; neologism